(untitled) (Pedagogy of Higher and Secondary Education, 2022)
In this article the author gives the definition of self-dependence (independence) via numerous scientific conceptions, where closely-related concepts are explained. To the closely-related concepts they bring self-actuality, self-respect, self-efficiency, self-organization, and besides the author opens and explains the meaning of each closely-related concepts, their importance and necessity due forming students’ self-dependence (independence) during the studying process.